The Removal of Methylene Blue from Aqueous Solutions Using Zinc Oxide Nanoparticles With Hydrogen Peroxide - Somayeh Bagheri; Fahimeh Moghadam; Hassn Mohammadi; Saeid Rigi (Hamadan University of Medical Sciences, 2023)
Industrial effluents produce vast amounts of pollutants and account for 20% of industrial wastewater annually. Methylene blue (MB) is one of the most widely used dyes in the medical, pharmaceutical, and textile industries. However, it is toxic to living organisms, and even a short-time exposure to it can be potentially harmful. Therefore, the purpose of this study was to investigate the efficiency of zinc oxide nanoparticles in removing MB from aqueous solutions in the presence of hydrogen peroxide. The effects of various parameters such as pH (3-10), ZnO nanoparticle dose (0.01-0.08 g/L), reaction time (5-50 minutes), initial concentration of MB (20-200 mg/L), and the hydrogen peroxide concentration (0.5-5 mg/L) were studied. The wavelength of maximum absorption (λmax) was 665 nm. The optimal pH value was 5, zinc oxide nanoparticle dose was 0.05 g/L, the initial concentration of MB was 40 mg/L, the concentration of hydrogen peroxide was 2 mg/L, and the contact time was 20 minutes. The efficiency of MB removal was 97.99%. The results showed that zinc oxide nanoparticles in the presence of hydrogen peroxide could remove the MB from aqueous solutions with high efficiency.